Comparative antioxidant potential of Withania somnifera based herbal formulation prepared by traditional and non-traditional fermentation processes - Jagdish Manwar; Kakasaheb Mahadik; L. Sathiyanarayanan; Anant Paradkar; Sanjay Patil (Integrative Medicine Research)
Background: Ashwagandharishtha is a liquid polyherbal formulation traditionally prepared by fermentation process using the flowers of Woodfordia fruticosa. It contains roots of Withania somnifera as a major crude drug. Alcohol generated during the fermentation causes the extraction of water insoluble phytoconstituents. Yeasts present on the flowers are responsible for this fermentation. Methods: Total nine formulations of ashwagandharishtha were prepared by fermentation process using traditional Woodfordia fruticosa flowers (ASG-WFS) and using yeasts isolated from the same flowers. During fermentation, kinetic of alcohol generation, sugar consumption, changes in pH and withanolides extraction were studied. All the formulations were tested for in vitro antioxidant potential by 1,1-diphenyl-2-picryl-hydrazyl (DPPH) free radical scavenging, hydrogen peroxide scavenging and total reducing power assay. The results were compared with standard ascorbic acid. Results: Traditional formulation (ASG-WFS) showed the highest activity (p < 0.001) relative to other formulations and standard ascorbic acid. ASG-WFS showed significant (DPPH) free radical scavenging (78.75%) and hydrogen peroxide scavenging (69.62%) at the concentration of 1000 μg/mL and 100 μg/mL, respectively. Conclusion: Traditional process is the best process for preparing ashwagandharishtha to obtain significant antioxidant activity.